PENERAPAN PENDEKATAN METAKOGNITIF UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN PRESTASI BELAJAR - Sumarti (UNIB Press, 2023)
This research aims to describe the application of Metacognitive Approach in improving Critical Thinking Skills, improving Learning Achievement, Effectiveness of Application of Metacognitive Approach can improve Learning Achievement in SMK Negeri 1 Jarai. The data analysis technique is Data Analysis of Observation of Implementation of Learning Approach and Critical Thinking Skills. U t-test test data analysis. And the results of Classroom Action Research by using cycles 1,2,3 which are combined in the experimental class and control class. The data collection technique used is the average learning completeness and test t-test. student achievement in the chemistry subject of class X TKJ students at SMK Negeri 1 Jarai. This can be seen from the results of the pre-test and post-test that always increase in each cycle. The application of a metacognitive learning approach can effectively improve chemistry learning achievement. This can be seen from the analysis of the results of the pre-test and post-test of each cycle and the results of the experimental class and control class. The results of the study conclude that this approach learning model improves critical thinking skills, learning achievenment and effectively improves student achievement in class X Chemistry learning at SMK Negeri 1 Jarai